2017 5th IEEE International Conference on Models and Technologies for Intelligent Transportation Systems (MT-ITS) 2017
DOI: 10.1109/mtits.2017.8005671
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of autonomous vehicles in urban networks and potential new capabilities for perimeter control

Abstract: Recently there has been an enormous effort towards the development and field deployment of autonomous vehicles (AV). These developments have a direct impact on road traffic characteristics, as AV can also be used as sensors, actuators, and generally as effective components of an online traffic management system. In this work, we explore through microsimulation how AV can affect the network performance on urban networks. It is demonstrated through simulation experiments, that for mixed traffic (i.e. AV and conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…The efficiency enhancement delivered by platoons on highways has been largely studied, however, there are not as many references detailing platoons in urban environments. Platoons on urban roads, with the support of communication for their formation and evolution, can reduce the saturation headway at signalized intersections ( 13 ). Lioris et al showed that the capacity can be analytically improved by the same factor as the increase in the saturation flow rate, with 100% CAVs ( 14 , 15 ).…”
mentioning
confidence: 99%
“…The efficiency enhancement delivered by platoons on highways has been largely studied, however, there are not as many references detailing platoons in urban environments. Platoons on urban roads, with the support of communication for their formation and evolution, can reduce the saturation headway at signalized intersections ( 13 ). Lioris et al showed that the capacity can be analytically improved by the same factor as the increase in the saturation flow rate, with 100% CAVs ( 14 , 15 ).…”
mentioning
confidence: 99%
“…One approach to represent the network MFD, which is adopted here, considers the total number of vehicles passing through the network (completing their trip) versus the total number of vehicles inside the network (which equals the density divided by the sum of all link lengths of the road network), within a specified interval. Alternatively, the total network production (veh · distance traveled per unit time) and accumulation (veh) can be calculated from loop detectors on links, where flows and densities are weighted by the length of the link ( 12 , 17 ). The first approach is preferred in homogeneously congested networks, whereas the second can be more accurate for the estimation of the average network speeds and densities in less homogeneously congested networks.…”
Section: Methodsmentioning
confidence: 99%
“…Three networks were used as testbed to demonstrate the feasibility of the proposed framework. The first network has been used in an earlier study ( 17 ) and corresponds to a part of the Cental Business District of Barcelona in Spain (Figure 2 a ). It consists of 1,570 sections and 565 signalized intersections.…”
Section: Application Of the Proposed Framework To Three Networkmentioning
confidence: 99%
See 2 more Smart Citations